Audiovisual Languages for Health. Social Representations of Obesity on TikTok: A Case Study - Lenzi, Francesca Romana; De Falco, Ciro Clemente; Iazzetta, Ferdinando; Esposito, Vincenzo; Capuano, Maria Elena (Italian Sociological Review, 2024)
Actors in the digital public sphere contribute to the public discourse on health and well-being by producing big data in various ways. User-generated health data are natural digital traces that social networks, wearable devices, health apps, and search engines can generate. The proliferation of user-generated content impacts the production, circulation, and consumption of health news, ensuring a vibrant public sphere on the topic. In today’s world, it is crucial to identify how new health-produced datasets can be used to assess Social Determinants of Health (SDH). SDH includes non-medical factors that influence health outcomes, such as the conditions in which people are born, grow, work, live, and age and what shapes the conditions of daily life. Health technologies hold great promise for developing digital health skills and improving health outcomes for patients with chronic diseases. Contemporary societies have undergone an epidemiological transition that has seen infectious-predominant diseases transform over the years into chronic-degenerative diseases. Social media provides an open forum for communication between individuals, and content creators on TikTok are progressively changing the way audiovisual texts are produced and enjoyed, following a logic that tends towards media convergence and intermediality. This article aims to conceptualize how influencers providing public health information promote knowledge related to the obesity debate. Based on a sample of TikTok videos, we can gather insights and interpretations that help analyze the messages and themes conveyed by social media influencers. This analysis can help us to identify information and dimensions relevant to health advocacy and shed light on the underlying discourses and themes in their content.